Pigeonpea improvement through conventional breeding - Wanjari, K. B.; Raje, R. S.; Durgesh, Kumar; Prashat, G. Rama; Joshi, Rekha (The Indian Journal of Genetics and Plant Breeding, 2017)
Contributions made through conventional breeding havebeen of great significance in the development of pigeonvarieties for diverse agro ecological regions in the country.The available genetic variability has been exploited to itsfull potential for enhancing trait based genetic improvement.However, the on farm productivity and production hasremained low due to several constraints including the plantarchitecture, early maturity, disease and insect pestresistance. Hence, to breed cultivars having high agronomicperformance with broad genetic base for specific regions,new sources of genetic variability need to be tapped. Wildspecies of Cajanus present a vast reservoir of useful genesfor pigeonpea improvement. Heterosis breeding hasenormous scope to break the yield barrier and enhancingpotential but there is great need to identify heterotic parentsto be used as MS lines and their respective restorers.However the major challenges are still being faced to answergenetic solutions for achieving yield potential through earlymaturity restructuring the plant type and resistancebreeding to pave the way for sustainability in pigeon peaproduction.